2006
DOI: 10.1111/j.1365-2966.2006.10182.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the Fornax dwarf spheroidal have a central cusp or core?

Abstract: The dark matter dominated Fornax dwarf spheroidal has five globular clusters orbiting at ~1 kpc from its centre. In a cuspy CDM halo the globulars would sink to the centre from their current positions within a few Gyrs, presenting a puzzle as to why they survive undigested at the present epoch. We show that a solution to this timing problem is to adopt a cored dark matter halo. We use numerical simulations and analytic calculations to show that, under these conditions, the sinking time becomes many Hubble time… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
351
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(370 citation statements)
references
References 31 publications
(35 reference statements)
15
351
2
2
Order By: Relevance
“…However, observations of dark mat-ter dominated systems, where subtracting off the baryons is less problematic, have yet to find convincing evidence of these cusps. Rather, they tend to favour shallower inner density slopes α ∼ < 0.5 both in low-mass galaxies (e.g., de Blok et al 2001;Swaters et al 2003;Goerdt et al 2006;Walker & Peñarrubia 2011;Oh et al 2011) and galaxy clusters (e.g., Newman et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, observations of dark mat-ter dominated systems, where subtracting off the baryons is less problematic, have yet to find convincing evidence of these cusps. Rather, they tend to favour shallower inner density slopes α ∼ < 0.5 both in low-mass galaxies (e.g., de Blok et al 2001;Swaters et al 2003;Goerdt et al 2006;Walker & Peñarrubia 2011;Oh et al 2011) and galaxy clusters (e.g., Newman et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, dwarfs and low surface-brightness galaxies suggest a much shallower profile with a relatively flat slope (α ≥ −0.5 with ρ(r) ∼ r α ) (Palunas & Williams 2000;Salucci & Burkert 2000;de Blok et al 2001;Swaters et al 2003;Gentile et al 2004;Spekkens et al 2005;Goerdt et al 2006;Walter et al 2008;Oh et al 2011;Walker & Peñarrubia 2011). On the other extreme of the halo mass scale, galaxy clusters tend to have a central cusp, as evidenced by studies combining strong and weak lensing (e.g., Limousin et al 2007;Leonard et al 2007; Umetsu et al 2007), but shallower slopes than the NFW one can also be found within the inner ≈ 5 kpc (Sand et al 2004;Sand et al 2008;Newman et al 2009;Newman et al 2011;Newman et al 2013;Richtler et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A particularly interesting particle mass range for the sterile neutrino can be framed by the mass required to produce a constant density core of 100-300 pc like that discussed for the Fornax dwarf spheroidal [3,4], which is 0.5-1.3 keV [5,34], or more massive if the phasespace packing limit is not achieved. In addition, the requirement for a viable sterile neutrino dark matter can-didate constrains their parameter space by demanding that: 1) the total decay time-scale is larger than the age of the universe, 2) it is consistent with radiation energy density constraints from primordial nucleosynthesis and the cosmic microwave background, 3) it is consistent with lithium photoproduction constraints, and 4) it is consistent with the diffuse X-ray background, and X-ray observations of of clusters or other nearby structures [35,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Several indicators point towards a modification of the properties of dark matter clustering from the cold dark matter (CDM) paradigm to resolve potential discrepancies that persist with the ansatz of an absolutely cold dark matter candidate. Among potential problems with CDM are indications for density cores in local group dwarf spheroidal galaxies [3,4,5,6] and the lack of a correspondence of the observed dwarf galaxies with the number of halos expected with the same maximal velocity dispersion or mass [7,8]. This has prompted the investigation of alternatives to CDM, such as warm dark matter (WDM) [9,10], late-decaying superWIMP dark matter [11,12], fuzzy cold dark matter [13], or meta-CDM [14].…”
Section: Introductionmentioning
confidence: 99%